Congenital Heart Disease In Preterm Infants - A Jassam, Maymouna; S. Mahmood, Najdat; Q. Mahmood , Sura (Diyala Journal of Medicine, 2023)
Background: Congenital heart defects and preterm birth are two important causes of neonatal and infant mortality. However, the relationship between them has not yet been fully clarified. Objective: To find the association of congenital heart disease with premature delivery. Patients and Methods: The study is an observational cross sectional study, done in Al-Batool teaching hospital for maternity and children from July 2022 to January 2023. A self-prepared questionnaire was used to gather data. Gestational age was calculated mainly on postnatal gestational assessment by Dubowitz/Ballard method by a pediatrician. Echocardiography was done by Echocardiography specialist doctor to identify the presence and types of congenital heart defects. SPSS version 25 was used for statistical analysis. Results: Total number of births (term and preterm) was 1616, congenital heart diseases were detected in 60(3.71%) of them, most of them were isolated heart defect. In preterm babies, the congenital heart diseases were detected in 8% (p value was <0.001), they were of different types as followings: patent ductus arteriosus (n=10,26%), atrial septal defect (n=8,21%), ventricular septal defect (n=7,18%), transposition of the great arteries (n=4,10%), tetralogy of Fallot (n=2,5%), and complex of congenital heart disease (n=7,18%), while in full term babies, the rate of congenital heart diseases was only 1.9%. Conclusion: The incidence of congenital heart disease was higher in preterm than full term delivered babies, mostly in the group of transposition of the great arteries, ventricular septal defect, complex heart defects, followed by atrial septal defect.